Preliminary study on heavy metals contents in edible seaweed solid in Kuching, Sarawak - Siti Nadiah, binti Salleh (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The aim of this study is to determine the heavy metals that present in edible seaweed sold at selected Kuching Local Market. Four markets from Satok, Santubong, Telaga Air and Muara Tuang were selected for this study. The concentration level of cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), iron (Fe) and zinc (Zn) were determined using Atomic Absorption Spectroscopy (AAS). There were three species of edible seaweed were identified in this studies namely Graci/aria changgi, Graci/aria coronopifolia and Graci/aria edulis. The concentration ofmetal ranged from 0.93 -8.26 mg/kg (Cd), 2.35 -7.29 mg/kg (Cr), 0.17 -4.62 mglkg (Cu), 2.26 -7.88 mglkg (Pb), 46.91 -87.24 mglkg (Fe) and 11.53 -74.62 mg/kg (Zn). The concentrations of heavy metals were also compared with the Malaysian Food Act, 1983 (MFA, 1983) and Food Agriculture Organization/World Health Organization, 1984 (FAOIWHO, 1984). The concentration of heavy metals such as Pb and Cd were exceeded permissible limit of MFA, 1983. Statistical analysis ofOneWay ANOVA showed there is no significance difference (p >0.05) between heavy metals contents in all the samples analyzed. Pb and Cd have potential to cause poisoning and affecting human health. However, there is no report regarding heavy metals poisoning from seaweed in Malaysia.